Analysis of the Influence of Physical Environment, Service Quality, and Satisfaction on Revisit Intention at Resort in Batam City - Dewirahayu Sad Wijaya; Ratih Anggraini (Politeknik Pariwisata Makassar, Indonesia, 2023)
The COVID-19 pandemic has negatively affected the tourism and hospitality industry in Indonesia. Many businesses have closed to help keep the virus under control, such as shopping centers and tourist attractions. Staycation can be a profitable business for tourism opportunities during the COVID-19 pandemic. Staycation has increased the popularity of hotels and resorts in Batam City. The study aims to help develop the world of tourism, especially in resort lodging in Batam City by exploring the influence of the physical environment, service quality, and satisfaction on revisit intentions at resorts in Batam City. The study used a quantitative approach by examining various variables and analyzed through a sampling process. The research respondents are local and domestic tourists who have previously had a staycation in Batam City. There were 1,883,244 tourists visiting Batam City in 2018 according to BPS data. The sample size in the population was calculated using the Sloven formula to obtain a sample of 440 respondents using Google Form Questionnaire disseminated through social media. IBM SPSS 25.0 software was used to analyze the collected data and test the hypothesis. The results showed that there is a significant positive influence between the physical environment, service quality, and satisfaction on revisit intention. Resort business owners need to understand the concept of staycation and the importance of improving products, services, and satisfaction to customers in order to create customer revisit intentions.